-8(u-86)+15=-65

Simple and best practice solution for -8(u-86)+15=-65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8(u-86)+15=-65 equation:


Simplifying
-8(u + -86) + 15 = -65

Reorder the terms:
-8(-86 + u) + 15 = -65
(-86 * -8 + u * -8) + 15 = -65
(688 + -8u) + 15 = -65

Reorder the terms:
688 + 15 + -8u = -65

Combine like terms: 688 + 15 = 703
703 + -8u = -65

Solving
703 + -8u = -65

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-703' to each side of the equation.
703 + -703 + -8u = -65 + -703

Combine like terms: 703 + -703 = 0
0 + -8u = -65 + -703
-8u = -65 + -703

Combine like terms: -65 + -703 = -768
-8u = -768

Divide each side by '-8'.
u = 96

Simplifying
u = 96

See similar equations:

| p=h+5 | | 19=3(n+2)+1 | | (2x-3)=(x+16) | | 15x-2x+3=10 | | 3p+8-7p= | | -7(5x+5)+4x=3x | | 7y-x=9 | | .024a-8=.224a+2 | | 3(m-8)+-2=8 | | 6x+35=8x+15 | | 8t+2m=w-8 | | -22+t=36 | | -4(2t+2)=-32 | | -4(-6x+1)-3x=1 | | 25z-15=6z-14 | | .03x-3.9=.66 | | 7x+3x=5x+50 | | 8x+8-6x=-6 | | 25z-15=6z-24 | | 4=2(g-11)-2 | | (-7p)3= | | 2=7x-26 | | 15-g=6 | | -6+3(-8x+1)=15 | | 3(f-8)=-24 | | .04m=.08 | | 5t(10-3t)= | | 7/x-4=14/6 | | -5(4x-1)=-3x-6 | | 7-k=5 | | -7x-13+9x-19=-4 | | -1=2(j-8)+1 |

Equations solver categories